Аналітичний огляд конструкцій електрокальцинаторів для термічної обробки вуглецевих матеріалів у щільному шарі - Безуглий, Володимир (Physico-technological Institute of Metals and Alloys, 2023)
The designs of existing in the world electric calciners – direct heating electric furnaces – for thermal treatment of carbon materials in a dense layer, namely, anthracite and petroleum coke were considered and analyzed in the article. The world annual production of thermoanthracite and calcined petroleum coke is tens of millions of tons and the number of operating electrical calciners in the world is many hundreds. Electrical calciners allow to obtain heat treatment temperatures of more than 1500 °С and have a high efficiency, since heat is released directly in the processed material during the passage of electric current. As a rule, heating in them occurs not only due to electric energy, therefore, strictly speaking, these furnaces can be combined according to the method of heating. Since only electrical heating makes it possible to obtain such high processing temperatures, in this article, electrical calciners include furnaces that not only fully, but also partially use direct electrical heating of the processed carbon material. The disadvantages of existing electric calciners lead to a significant excess demand energy during heat treatment, to a significant variation in the properties of the treated material and to a significant loss by burning. The causes of these disadvantages were identified and analyzed. According to the author of the article, promising areas for improving electrical calciners with dense layer are: use of a multielectrode design with electronically controlled current density inside the working volume in ELKEM type furnaces and improvement of the design of Carbone Savoie type furnaces, aimed at ensuring the safety of their operation and intensifying the process of the regeneration of physical heat. There is also a significant potential for further development of technologies for the heat treatment of carbon materials in a dense layer, which can be implemented in furnaces with new principles, operation schemes and designs.